The martyrial face of the salvadorean church from the theological biographies of Oscar Romero and Ignacio Ellacuría: a revaluation of the prophetic dimension in the ordained ministry - Mauti, Ricardo Miguel (2024)
Fil: Mauti, Ricardo Miguel. Pontificia Universidad Católica Argentina. Facultad de Teología; Argentina